Treatment Outcomes of Quality of life and Nasolabial Appearance in Patients with Cleft Lip and Palate of 10-Year-Old Group - Surakunprapha, Palakorn; Pradubwong, Suteera; Paggasang, Yupin; Jenwitheesuk, Kamonwan; Pisek, Poonsak; Chowchuen, Bowornsilp (Srinagarind Medical Journal, 2021)
Background and Objectives: Cleft lip and palate (CLP) requires a long term management from an interdisciplinary team since it affects the quality of life (QoL) and nasolabial appearance in patients during puberty. Methodology: The descriptive studies in 10–year-old group of patients with CLP who received treatment care from Tawanchai Center, Srinagarind Hospital, during the Year 2017-19, a total of 30 cases. The tool was a five-aspect QoL questionnaire with39 items with a reliability of 0.94, photos of patients face in frontal and lateral sides to assess nasolabial appearance in 4 dimensions. The score of aesthetics rating scale of 5 levels from 5 raters was gathered. The data were analyzed by using percentage statistics, mean and standard deviation. Results: It was found that 53.3% of the patients were male, 63.3 percent of the total UCLP. Most of the parents were primary caregivers and73.3 percent of the parents completed primary school. The family income per month was in the range of 5,001-10,000 baht (30percent). While the QoL in 5 aspects showed the satisfaction level as follows; the service was at the highest level (4.30 ± 0.98), medical treatment and expenses was at a high level (3.72 ± 1.15), (3.70 ± 1.14), the parents in the psychosocial dimension, and the impact on the family was moderate (3.33 ± 1.08), (2.81 ± 1.46). As for the nasolabial appearance most of them had a good average score 53.3 percent. Conclusion: Most of the patients were male and had UCLP. Parents had 3 aspects of good to very good QoL and 2 moderate levels. Most of them had a good to average nasal appearance.